Assessing the synergistic effect of “pollution and carbon reduction” and “economic growth”: a perspective from bilateral trade between China and RCEP countries - Wen, Ya; Shu, Ruijie; Gao, Chen; Yan, Shiling (Frontiers in Environmental Science, 2024)
With the accelerating process of globalization, trade activities have had profound impacts on both the environment and economic development. This paper comprehensively evaluates the synergistic effect of bilateral trade on "pollution reduction" and "carbon mitigation," as well as "economic growth," utilizing panel data from China and RCEP countries spanning the period from 1997 to 2020. The empirical results reveal that bilateral trade significantly propels economic growth in RCEP countries and exhibits a positive "pollution reduction" effect, whereas its "carbon reduction" effect remains uncertain. To delve into the underlying reasons for bilateral trade's failure to effectively mitigate carbon emissions, this paper undertakes a mechanism test along two opposing paths. Notably, the influence of bilateral trade on economic growth and "pollution reduction" in RCEP countries varies regionally. Specifically, bilateral trade is more efficacious in fostering economic growth in ASEAN countries. Additionally, bilateral trade enhances environmental quality in ASEAN countries, yet it deteriorates in non-ASEAN countries. Furthermore, this paper examines the intricate relationship between bilateral trade, economic growth, and "pollution reduction" through the application of the PVAR model. It concludes that optimizing environmental quality in RCEP countries is conducive to both local economic growth and bilateral trade. This study not only bears significant implications for understanding the complex interplay between economic growth, environmental quality, trade liberalization, and environmental policies, but also provides invaluable guidance for policy formulation and implementation aimed at achieving green transformation and fostering sustainable economic development.